2019
DOI: 10.1016/j.scitotenv.2019.01.219
|View full text |Cite
|
Sign up to set email alerts
|

As release under the microbial sulfate reduction during redox oscillations in the upper Mekong delta aquifers, Vietnam: A mechanistic study

Abstract: Highlights: Microbial sulfate reductionwas found to contribute to arsenic (As) sequestration; During anoxic conditions, the conversion of soluble As(V) to As(III) was observed; The formation of pyrite, rather than mackinawite was observed in redox cycles; Absorption/desorption of aqueous As on Fe-(oxyhydr)oxides and pyrite was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 116 publications
(125 reference statements)
1
6
0
Order By: Relevance
“…Berg et al, 2001;Smedley and Kinniburgh, 2002;Ravenscroft et al, 2009;Benner and Fendorf, 2010;Winkel et al, 2011). Many studies have revealed that the mobilization of As into groundwater is related to natural processes, of which the microbially driven oxidation of organic matter coupled with the reduction of As-bearing Fe(III) (oxyhydr)oxides in the deltaic sediments is the most dominant and well-studied mechanism (Nickson et al, 2000;McArthur et al, 2001;Dowling et al, 2002;Harvey et al, 2002;Akai et al, 2004;Islam et al, 2004;Swartz et al, 2004;Postma et al, 2007Postma et al, , 2010Postma et al, , 2012Fendorf et al, 2010;Stuckey et al, 2015;Phan et al, 2019;Glodowska et al, 2020a). A characteristic feature of the As contaminated areas is that orange, often Pleistocene aquifer sands mostly show As groundwater concentrations below the WHO limit of 10 g/L, while gray, mostly Holocene sandy aquifers have dissolved As concentrations 10 to 30 times the WHO limit (Berg et al 2001;van Geen et al, 2013;Jung et al 2015;Stopelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Berg et al, 2001;Smedley and Kinniburgh, 2002;Ravenscroft et al, 2009;Benner and Fendorf, 2010;Winkel et al, 2011). Many studies have revealed that the mobilization of As into groundwater is related to natural processes, of which the microbially driven oxidation of organic matter coupled with the reduction of As-bearing Fe(III) (oxyhydr)oxides in the deltaic sediments is the most dominant and well-studied mechanism (Nickson et al, 2000;McArthur et al, 2001;Dowling et al, 2002;Harvey et al, 2002;Akai et al, 2004;Islam et al, 2004;Swartz et al, 2004;Postma et al, 2007Postma et al, , 2010Postma et al, , 2012Fendorf et al, 2010;Stuckey et al, 2015;Phan et al, 2019;Glodowska et al, 2020a). A characteristic feature of the As contaminated areas is that orange, often Pleistocene aquifer sands mostly show As groundwater concentrations below the WHO limit of 10 g/L, while gray, mostly Holocene sandy aquifers have dissolved As concentrations 10 to 30 times the WHO limit (Berg et al 2001;van Geen et al, 2013;Jung et al 2015;Stopelli et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Several factors such as seasonal variations or pumping-induced changes in groundwater head and groundwater flow direction, or the type and availability of organic matter are known to influence the prevalent redox state of the aquifer (e.g. Jung et al, 2015;Stuckey et al, 2015;Eiche et al, 2017;Schaefer et al, 2017;Phan et al, 2019). Highly variable sedimentology, including fluviatile channel fillings and the interfingering of marine and fluviatile deposits of different grain size, can also be responsible for highly contrasting redox subsurface conditions on centimeter-to meter-scales (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In the phosphogypsum experiment, Fe 2+ in solution first decreases in the oxic half cycles as Eh increases, and free Fe 2+ oxidatively precipitates as FeOOH, a phenomenon catalysed by adsorption of Fe 2+ on mineral surfaces (Silvester et al, 2005), or as amorphous Fe 3+ phosphates. The oxidation of Fe 2+ originating from pyrite oxidation and Fe-(oxyhydr)oxides to Fe 3+ phases was, also, described in similar studies (e.g., Phan et al, 2019). The rapid precipitation of poorly crystalline Fe 3+ minerals under oxic conditions has been described by Megonigal et al (2003).…”
Section: Fe and S Redox Processes' Effect On Metal Behaviourmentioning
confidence: 57%
“…The experiment was performed using a custom two part Pyrex® glass redox stat bioreactor system designed by Thompson et al (2006) and modified later by Parsons et al (2013); the system was also used in similar, recent studies (Markelova et al, 2018;Phan et al, 2018;2019) (Fig. 2).…”
Section: Experimental Set-up and Sample Treatmentmentioning
confidence: 99%
“…Sediment redox processes are dynamic and the role of oscillating redox condition on the diffusion and retention of As across the sediment-water boundary has been the focus of substantial research (Arsic et al, 2018;Bennett et al, 2012;Johnston et al, 2020;Parsons et al, 2013;Phan et al, 2019). These studies have typically explored the mechanics of As mobility using laboratory experiments where oxygen conditions have been manipulated in soil or sediment incubations.…”
Section: Fluxes Of As Across the Sediment-water Boundarymentioning
confidence: 99%